Main mechanisms and features of epileptogenesis of post-traumatic epilepsy - S. A. Antonenko (Kazimierz Wielki University, 2019)
One of the most frequent and formidable consequences of traumatic brain injury (TBI) is post-traumatic epilepsy (PTE), which is the main identified cause of symptomatic epilepsy at a young age. The work highlights the "trigger" mechanisms of brain damage, including oxidative stress, leading to the disintegration of all levels of the central nervous system, contributing to the development of neuropathological syndromes, and especially PTE. The questions of differentiation of PTE from other epileptic paroxysms, the dependence of the development of PTE on the severity of TBI, the main risk factors for this type of epileptogenesis, its phasing, as well as disorganization and damage to the antiepileptic system are considered. The place of a nonspecific response to damage in the form of immediate and early seizures, their metamorphosis as the formation of PTE was determined. The existing spectrum of convulsive seizures is described, including partial, taking into account the localization characteristic of TBI with a predominance of lezional forms.